Theoretical and methodological basis of continuous culture of microorganisms - Malek, Ivan; Fencl, Zdenek (Pub. House of the Czechoslovak Academy of Sciences ; Academic Press, 1966)
Theoretical and Methodological Basis of Continuous Culture of Microorganisms deals with the continuous cultivation of microorganisms. The book contains six chapters and opens with a discussion of the origins, principles, and development of continuous cultivation methods. This is followed by separate chapters on continuous systems (open, closed, semi-continuous systems), theoretical analysis of continuous culture systems, techniques of continuous laboratory cultivations, experimental applications of continuous cultivation, and industrial continuous fermentations.